Implementation of Physical Test Results Measurement Using a Pencak SIlat Sports Web Application - Afriyanti, Faradillah Dwi; Hartati, Hartati; Deatriana, Destriana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
This research constitutes a quantitative descriptive study employing a survey method, specifically a fitness test administered to sixth-grade students at State Elementary School 112 Palembang. The primary objective of this study is to establish normative categories for assessing the physical fitness of students in the sport of pencak silat using a dedicated application. The key components evaluated in the context of pencak silat are strength, speed, agility, flexibility, and endurance. The study involved 30 participants, comprising 11 male students and 19 female students. Test instruments for data collection included the sit-up test for assessing strength, the 30-meter running test for speed, the agility t-test for agility, the sit and reach test for flexibility, and the bleep test for endurance. The collected data underwent analysis using quantitative descriptive techniques. The research findings revealed that the strength test results fell into the poor category, speed into the very poor category, agility into the sufficient category, flexibility into the very poor category, and endurance into the very poor category. Consequently, the overall assessment of the physical condition of sixth-grade students at State Elementary School 112 Palembang indicates a very poor category. In summary, the study concludes that the average physical fitness of class VI students at State Elementary School 112 Palembang is deemed very poor. It is recommended that appropriate exercises be implemented to enhance the physical fitness of the students.